2009
DOI: 10.1007/s00027-009-9182-6
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on biogeomorphology, ecosystem engineering and self-organisation in island-braided fluvial ecosystems

Abstract: Using the River Tagliamento, Italy, as an example, we examine the role of self-organisation in the formation and dynamics of vegetated islands in fluvial ecosystems. We consider how various biogeomorphic processes, such as feedbacks between tree growth and sedimentation, influence island self-assembly, as well as the potential influences of island landforms on resource distribution and shifts in ecosystem state. Despite the abundance of island landforms of different sizes and ages in island-braided reaches alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
103
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 116 publications
(199 reference statements)
0
103
0
Order By: Relevance
“…Cottonwood currently combines 'r' (ruderal opportunistic) traits at the juvenile stage with K (competitive) traits at the adult stage when it reaches its sexual maturity on stabilized surfaces. The initial abiotic conditions selected the r traits in the long term, whereas the K traits may correspond to an evolutionary feedback associated with engineer effects [28]. Thus, even if the described engineer effects may seem to be negative in the short term, they appear to be rather positive in the long term.…”
mentioning
confidence: 97%
“…Cottonwood currently combines 'r' (ruderal opportunistic) traits at the juvenile stage with K (competitive) traits at the adult stage when it reaches its sexual maturity on stabilized surfaces. The initial abiotic conditions selected the r traits in the long term, whereas the K traits may correspond to an evolutionary feedback associated with engineer effects [28]. Thus, even if the described engineer effects may seem to be negative in the short term, they appear to be rather positive in the long term.…”
mentioning
confidence: 97%
“…The results indicated that in the context of this study site, the heterogeneity in relief (LHI1, LHI2 and LHI3) showed the most frequent relationships with the ecological variables followed by heterogeneity in slope (LHI4, LHI7, LHI8), aspect The heterogeneity of geomorphic and ecological processes provides resilience of these systems to small disturbances through system adjustments (Simon, 1998, Francis et al, 2009). Multi-scale and multi-dimensional relationships between topographic differentiation, soil properties and vegetation are known to exist (Solon et al, 2007).…”
Section: Most Influential Lhis Landform Characteristics and Responsimentioning
confidence: 88%
“…Biogeomorphic interactions are believed to be at the roots of ecosystem state transitions (Francis et al, 2009) and hence it may have great potential in assessment of rehabilitation of mined lands. The relief features and ecological processes interact with each other in such a way that the entire system appears to work through a self-regulating.…”
Section: Co-evolution Of Landforms and Ecosystemsmentioning
confidence: 99%
See 2 more Smart Citations